Water in the COVID-19 crisis: Response, recovery, and resilience - Sadoff, Claudia; Smith, Mark (International Food Policy Research Institute, 2020)
COVID-19 has, like nothing that has gone before, revealed the “systems wiring” of the modern, globalized world, and how destructive disturbances to those systems can be. Water is a connector across these systems, and thus has critical implications for both the effectiveness of COVID-19 response efforts and for promoting growth and building resilience in a post-pandemic world.